Intra-articular Glenoid Fracture Managed by Arthroscopic Fixation and Open Reduction and Internal Fixation Techniques: An Analytical Study - Prahalad K Singhi; Sivakumar Raju; Chidambaram Muthu; Gopi Kumarasamy; Vinoth Thangamani; Muthukishore Marichamy (Journal of Orthopedics and Joint Surgery)
Introduction: Intra-articular glenoid fractures are rare injuries. Due to complex anatomy and neurovascular structures in vicinity, operative treatment is relatively uncommon. With the advent of three-dimensional (3D) computed tomography (CT), appropriate analysis of fracture pattern and management protocols can be developed. Operative treatment has evolved from extensive open reduction to arthroscopic surgery. Here, we analyzed the intra-articular glenoid fractures, which were managed by conservative, open, or arthroscopic fixation (ARIF) to derive a treatment algorithm. Materials and methods: All the shoulder fractures which presented to our hospital from January 2018 to December 2020 were screened for intra-articular glenoid fractures. An institutional treatment algorithm was followed for 10 such fractures, where four underwent ARIF, four by open reduction, and two were conserved. These patients were followed up, and functional evaluation with Constant–Murley and the University of California, Los Angeles (UCLA) scoring system were done. Results and discussion: The mean constant score at 1 and 2 years follow-up were 63.2 ± 9.3 and 78 ± 9.7, respectively. The mean UCLA score at 1 and 2 years follow-up were 23.7 ± 4.4 and 28.3 ± 3.7, respectively. At the end of 2 years’ follow-up, all these patients had good to excellent outcome. One patient had shoulder stiffness; clavicle elastic nail was removed in two cases as it caused irritation at entry site and no other major complications. Conclusion: Intra-articular glenoid fractures are uncommon injuries but can end up in severe morbidity if neglected or not aptly treated. Anatomical restoration of the articular surface is the goal in management of intra-articular glenoid fractures. Undisplaced fractures or articular step-off <2 mm can be managed conservatively. Even the undisplaced glenoid fracture needs fixation if there is a double disruption of scapulothoracic suspensory complex (SSSC). Displaced intra-articular fractures without extending into scapular body and double disruption of SSSC can be managed with ARIF. Intra-articular glenoid fracture extending to scapular body or double disruption of SSSC warrants open surgery. Clinical significance: We report a single-center study with treatment algorithm for surgical management and decision-making in intra-articular glenoid fractures, which remains challenging.